Posyandu cadres roles and complete basic immunization coverage in Muara Teweh Community Health Center - Nathalia, Ayu; Meldawati; Wahdah, Rabia (Ananda - Health & Education Foundation, 2025)
Background: Complete basic immunization remains a critical public health intervention to reduce infant morbidity and mortality. In Indonesia, immunization coverage remains below the national target, especially in remote regions such as Muara Teweh, Central Kalimantan. Posyandu cadres—community health volunteers—are essential actors in promoting immunization at the grassroots level. However, the effectiveness of their roles has not been consistently evaluated. Objective: This study aimed to assess the association between the roles of Posyandu cadres—both during Posyandu sessions and outside regular activities—and the achievement of complete basic immunization coverage in Muara Teweh Comuunity Health Center. Method: A quantitative cross-sectional study was conducted involving 32 Posyandu cadres in Kelurahan Pangkuh Raya. Total sampling was applied. Data were collected using a structured, validated questionnaire assessing cadre roles and immunization status, verified through Posyandu and Mother and Child Health records. Data analysis involved Chi-Square and Fisher’s Exact tests, with significance set at p < 0.05. Result: The findings revealed that 68.7% of infants had complete basic immunization. Most cadres (78.1%) were highly involved during Posyandu, and 87.5% were active outside it. However, statistical analysis showed no significant relationship between cadre roles during (p = 1.000) or outside (p = 0.465) Posyandu and immunization coverage. Conclusion: While cadre involvement was generally high, it did not significantly impact immunization outcomes. Future interventions should focus on improving cadre communication skills, addressing contextual barriers, and integrating supportive systems to enhance immunization effectiveness in remote settings.